Analisis Fiqih Wakaf Kontemporer di Indonesia - Azizah Mursyidah (Institut Agama Islam Sahid (INAIS) Bogor, 2022)
This study aims to determine the analysis pillars of waqf fiqh past and present, as well as what objects distinguish between waqf past and present, the aim is to compare and adjust the times, the method used is descriptive qualitative research, it can be concluded that the results of this study are, waqf Previously, there was no nazdir, while the waqf constitution required nadzir, and waqf objects were only limited to 3M (mosques, tombs, madrasa), now they have developed into movable assets, such as money, gold, securities, buildings, and vehicles.